Unravelling nanostructured Nb-doped TiO2 dual band behaviour in smart windows by in situ spectroscopies. Issue 37 (17th July 2022) - García-Tecedor, Miguel; Gorni, Giulio; Oropeza, Freddy; Gómez, Laura; Liras, Marta; de la Peña O'Shea, Victor A.; Barawi, Mariam
Abstract : Nb doped TiO2 NCs exhibit a selective modulation in the VIS and NIR regions associated with polaronic and plasmonic absorptions. Comprehensive in situ electrochemical XAS, spectroelectrochemistry and EIS experiments allow us to unravel and independently study these two phenomena. Abstract : Nb doped TiO2 nanocrystals (NCs) are one of the most attractive candidates for energy-efficient smart window devices due to their ability to provide a selective modulation of the optical transmittance in the visible and near infrared regions. This dual functionality is associated with two independent bulk (polaronic absorption) and surface (plasmonic absorption) electrochemical charging processes. However, there are still some unclear aspects such as the real role of Nb 5+ in the electrochemical reduction of anatase TiO2 and the chemical changes experienced by the dopant during this reaction. Herein, a comprehensive in situ X-ray absorption spectroscopy study has been employed to unveil the more effective reduction of the doped anatase and the significant reduction of the Nb 5+ dopant to Nb 4+ under electrochemical reaction conditions. Additionally, an exhaustive electrochemical impedance spectroscopy and in situ spectroelectrochemistry study on a lab-scale smart window device sheds light on the dual polaronic and plasmonic charge accumulation processes occurring in these NCs during operation.